A quantitative Analysis of Energy Security Performance by Brazil, Russia, India, China, and South Africa in 1990-2015 - Bogoviz, Aleksei V.; Ragulina, Yulia V.; Lobova, Svetlana V.; Alekseev, Alexander N. (International Journal of Energy Economics and Policy, 2019)
The paper addresses the gap existing in the scholarship and provides an analysis of the energy security performance made by the group of BRICS (Brazil, Russia, India, and South Africa) over the total of 25 years, from 1990 to 2015. The research is based on a comprehensive approach to understanding energy security as the total of four dimensions: availability, efficiency, affordability, and environmental stewardship. An energy security performance index operationalizes each dimension of energy security with three indicators, which allows to quantitatively measure the progress made by the group of BRICS in terms of ensuring their energy security. The research conducted surprisingly shows that the overall energy security of BRICS as a group of states has not changed over the years. However, each country has experienced considerable changes in energy security performance, with the most dramatic ones made by Russia (growth) and China (decline). Keywords: Energy Security, Index, BRICS JEL Classifications: Q2, Q3, Q4 DOI: https://doi.org/10.32479/ijeep.7585